2002
DOI: 10.1046/j.1523-1747.2002.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the High-Affinity Choline Transporter, CHT1, in the Neuronal and Non-neuronal Cholinergic System of Human and Rat Skin

Abstract: Choline is an essential component in acetylcholine biosynthesis, and is involved in cell signaling. It is unable to permeate the cell membrane and requires a transporter to enter the cell. Neurons that synthesize acetylcholine take up choline by a recently cloned high-affinity choline transporter (choline transporter 1) that is Na+-dependent and can be blocked by hemicholinium-3. The aim of this study was to determine the expression and to analyze the distribution of choline transporter 1 in human and rat skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…Recently, CHT1 immunoreactivity has been identified in human keratinocytes and HaCaT cells (9) and in ciliated cells of the tracheal epithelium (7) by immunohistochemistry. These authors suggested that CHT1 is a novel component of the intrinsic non-neuronal cholinergic system of the skin.…”
Section: Up [mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, CHT1 immunoreactivity has been identified in human keratinocytes and HaCaT cells (9) and in ciliated cells of the tracheal epithelium (7) by immunohistochemistry. These authors suggested that CHT1 is a novel component of the intrinsic non-neuronal cholinergic system of the skin.…”
Section: Up [mentioning
confidence: 99%
“…CHT1 is a Cl − -and Na that is highly sensitive to the choline analogue HC-3, and it is thought to be part of the rate-limiting step in ACh synthesis. CHT1 is also expressed by subpopulations of non-neuronal cholinergic cells such as ciliated cells of the airway epithelium (7,8) and keratinocytes (9). However, functional studies have shown that the airway epithelial cell line A549 expresses both a Na + -dependent CHT1 and a lower-affinity Na + -independent choline transporter (10).…”
Section: Introductionmentioning
confidence: 99%
“…9). DISCUSSION Recently, the importance of small autacoids, primarily thought to be neurotransmitters, in mediating a variety of biological activities in the skin (9,(43)(44)(45) has been demonstrated. In particular, several studies have indicated that adenosine, via stimulation of its receptors, is involved in cell proliferation and cell death.…”
Section: Cl-ib-meca Inhibits Cell Proliferation and Erk1/2 Activation-inmentioning
confidence: 99%
“…CHT1 is also expressed in rat and human endothelial and smooth muscle cells (Lips et al, 2003). The mRNAs of choline acetyltransferase (the enzyme responsible for acetylcholine synthesis) and VAChT (the transporter responsible for loading acetylcholine into secretory vesicles and making acetylcholine available for release) are expressed in rat pulmonary arteries and in endothelial cells (ECs) isolated from human or porcine pulmonary blood vessels (Haberberger et al, 2002). Choline acetyltransferase protein is present and functional in primary cultures of human umbilical vein ECs (Kirkpatrick et al, 2003).…”
Section: Introductionmentioning
confidence: 99%